Un modelo de equilibrio general dinámico para la migración Boliviana: Qué sucede con la desigualdad de la riqueza? - Roberto Romano Burgoa (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2017)
– Migration has been a difficult phenomenon to measure because of its volatile characteristics and the number of models that explain the essential incentives of the process. In Bolivia there are few quantitative studies of international migratory movements, however, there are records that reflect a great socioeconomic impact by the migratory decisions. Throughout the document it describes that Bolivia has a negative migratory balance and that the profiles of the migrants have certain variable characteristics in the time. Generally, the search for accumulation of wealth, better living conditions, access to better education, better remuneration for productivity, among others, are sufficiently valid incentives to migrate to another developed country. The paper measures the impact of international migration on inequality of Bolivian wealth through the use of a dynamic general stochastic model DSGE with heterogeneous agents, specifying Argentina as the foreign economy because it is the country that holds most of the Bolivian people.
Keywords: D31; D59; D52; J11; J61; R23; 330; International Migration; Migration Profile; Migration Flows; Stochastic Dynamic General Equilibrium Model; Heterogeneous Agents; Inequality of Wealth; Labor Productivity